MiR‐873 inhibition enhances gefitinib resistance in non‐small cell lung cancer cells by targeting glioma‐associated oncogene homolog 1. Issue 10 (20th August 2018) - Jin, Shidai; He, Jing; Li, Jun; Guo, Renhua; Shu, Yongqian; Liu, Ping
Abstract : Background: The five‐year survival rate of non‐small cell lung cancer (NSCLC) patients is very low. MiR‐873 is involved in the growth, metastasis, and differentiation of tumors. Herein, we determined the target gene and influence of miR‐873 in NSCLC. Methods: MiRanda and Targetscan websites were used to predict the target gene of miR‐873 in NSCLC. Luciferase activity was examined using a dual luciferase reporter gene assay kit. The viability, tube formation, and proliferation of cells were analyzed by cell counting kit‐8, angiogenic analysis, and flow cytometry, respectively. The levels of miR‐873 and GLI1 were evaluated using quantitative real‐time PCR and Western blot assays. Results: Low levels of GLI1 and high levels of miR‐873 were observed in an NSCLC cell line (PC9) highly sensitive to EGFR‐tyrosine kinase inhibitors. There was a negative correlation between miR‐873 and GLI1 expression in PC9 and PC9/GR cells. The inhibition of miR‐873 enhanced GLI1 levels. MiR‐873 expression was inhibited by gefitinib. Gefitinib markedly reduced the viability, tube formation, and cell number in PC9 cells. However, suppression of miR‐873 enhanced the resistance and knockdown of GLI1 enhanced the sensitivity of PC9 cells to gefitinib. Conclusions: GLI1 is a target gene of miR‐873 in NSCLC. The inhibition of miR‐873 increased gefitinib resistance of NSCLC cells via the upregulation of GLI1 . These results indicate that miR‐873‐GLI1 signaling is involved in gefitinib resistance in NSCLC.